Pengaruh Brand trust dan Brand image terhadap Keputusan Pembelian pada Konsumen Produk Somethinc di Kota Tasikmalaya - Siti Nurlela; Suci Putri Lestari; Evilia Sri Yuniar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aimed to analyze the influence of brand trust and brand image on the purchase decisions of Somethinc products in Tasikmalaya City. The research employed a survey method with a quantitative approach and involved 100 respondents who had used Somethinc products. Path analysis was used to examine the simultaneous and partial effects of brand trust and brand image on purchase decisions, as well as the role of brand trust as a mediator. The results indicated that brand trust and brand image simultaneously had a significant effect on purchase decisions. Partially, brand trust and brand image also had a positive and significant influence on purchase decisions. Brand trust influenced the purchase decision through the brand image of Somethinc products in Tasikmalaya. It was suggested that companies strengthen brand trust and brand image by conducting periodic evaluations of the effectiveness of their strategies and monitoring the development of brand trust and brand image and their impact on purchase decisions.